(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This study investigates how AgTech startups influence the socio-economic and environmental aspects of farming in the Amravati Division. It evaluates the adoption levels, efficacy, and challenges of precision agriculture tools, highlighting the role of AgTech startups in facilitating technology integration for improved productivity and sustainability. A mixed-method approach was employed, combining quantitative survey with 250 farmers and qualitative interviews with AgTech industry stakeholders. Additionally, secondary data from case studies provided contextual insights into adoption trends, barriers, and impact assessment. Descriptive and inferential statistical analyses were applied to examine the relationships between technology adoption, economic benefits, and environmental sustainability. The study reveals moderate adoption of precision agriculture tools, with higher uptake in irrigation and soil monitoring technologies compared to advanced tools like drones and automated machinery. Key barriers include financial constraints, technical complexity, and limited training. Farmers who adopted precision agriculture reported increased yields (20-30%), reduced input costs, and improved resource efficiency. AgTech startups played a crucial role in promoting adoption through affordable solutions, training programs, and advisory support, though challenges related to scalability and compatibility persist. This research uniquely focuses on the relationship between farmers and AgTech startups in the Amravati Division, offering valuable insights into the factors driving or hindering the adoption of precision agriculture. The findings have broader implications for policy development, AgTech innovation, and sustainable agricultural practices in emerging economies.